THE EFFECTS OF COGNITIVE BEHAVIORAL INTERVENTIONS ON REMOVING BARRIERS TO TREATMENT ADHERENCE IN HEMODIALYSIS PATIENTS - Zolfaghari, Mitra; Sookhak, Fatemeh; Kashfi, Seyyed Hannan; SEKHAVATI, EGHBAL; Tabrizi, Reza (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Treatment adherence in chronic patients results in favorable treatment outcomes. Today, one of the main causes of mortality in hemodialysis patients is that of lack of treatment adherence. Identifying barriers to adherence to treatment is the first step to help these patients. The purpose of this study is to determine the effects of cognitive behavioral interventions on removing barriers to treatment adherence in hemodialysis patients. Methods: This clinical study was carried out in the hemodialysis wards of Imam Reza Hospital of Larand Vali-e-Asr Hospital of Lamerd. The sample included 70 patients who were randomly assigned into two groups of intervention (n=35 for even days)and control (n=35 for odd days). The intervention group received a six-step cognitive behavioral treatment. The level of barriers to treatment adherence was assessed using a self-report questionnaire in two stages (pre-intervention and post-intervention). Data were analyzed using SPSS via independent t-test. Results: Before the intervention, the two groups were not significantly different in terms of barriers to treatment adherence (p=0.68). However, after the treatment regimen, the barriers significantly decreased for the intervention group. There was a significant difference between the two groups in terms of barriers to treatment adherence (p<0.001). Conclusion: Given the efficacy of cognitive behavioral intervention, it can be used to identify barriers to adherence and design individualized education programs based on barriers to adherence in hemodialysis patients to increase their treatment adherence. Keywords: Cognitive behavioral, Barriers to treatment adherence, Hemodialysis patients.